Agroforestry interventions for soil and water conservation and ecorestoration - Dadhwal, K.S. (Indian Journal of Agroforestry, 2020)
Natural resources viz. soil, water, vegetation and climate are the most precious and very essential for agricultural productivity, environmental conservation, livelihood security and overall socio-economic prosperity. But, the land use in India face many challenges due to heavy demographic pressure on these resources. The extent of land degradation in country has been variously estimated to range from 53.28 to 187.7 million ha. Water erosion is a dominant factor causing 45% of land degradation which results a soil loss of 5.3 billion tonnes annually. Other factors causing land degradation is wind erosion (4.1 %), chemical deterioration (4.2%) and physical deterioration (3.6%). Soil erosion has both positive and negative effects. Positive effects may be formation of alluvial soils, improvement of soil depth, burial of inferior soil etc. but negative on-site and off-site effects are more severe and disastrous causing land degradation and environmental problems. The average erosion rate in the country has been estimated to be 16.4 t ha-1 yr-1 which is much higher than the permissible rate of soil erosion varying between 4.5 to 11.2 t ha-1 yr-1 depending upon soil, topography and climatic conditions. It calls for serious efforts to check the menace of land degradation to preserve the soil fertility and ensure environmental security, To combat this, plantation of multipurpose tree species (MPTS), shrubs, grasses, legumes, etc. are the effective and reliable measures. These agroforestry interventions, apart from checking soil degradation, also ameliorate soil characteristics (organic matter, texture, bulk density, pH, fertility build up, water holding capacity etc.) and enhance biomass production. An integrated watershed management approach comprising agroforestry practices and mechanical measures (wherever necessary) for managing degraded lands not only reduce runoff and soil loss but increase ground water recharge leading to better soil moisture conservation. Therefore, sustainable development and management of degraded lands through scientific agroforestry interventions has a great scope and potential in meeting out the various demands of growing human and livestock population for food, fodder, firewood, fibre, fertiliser, etc. apart from providing economic, environmental and livelihood security. In this context, it has been attempted to describe briefly the pertinent agroforestry interventions for managing degraded lands and arresting environmental degradation.